THE EFFECT OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE - Kenedi, Jon; Satriawan, Bambang; Khaddafi, Muammar (RADJA PUBLIKA, 2022)
The purpose of this research is to find out influencedimensions of organizational culture (professionalism, integrity, service user orientation, and continuous improvement) on the performance of the employees of the Port Authority and Port Authority of Tanjung Balai Karimun. In addition, this study aims to determine the dimensions of organizational culture that have the most influence on the performance of the employees of the Port Authority and Port Authority of Tanjung Balai Karimun. This study uses a quantitative descriptive approach with multiple regression analysis as the analysis technique. The results showed that organizational culture (professionalism, integrity, service user orientation, and continuous improvement) as a whole had a positive effect on employee performance. Meanwhile, for the partial test, the integrity variable has the most significant effect on employee performance.